Bilateral lung herniation with parenchymal infarction following clamshell thoracotomy for lobar lung transplantation: a case report - Tavandžis, Janis; Novysedlák, René; Pozniak, Jiří; Švorcová, Monika; Mošna, František; Vajter, Jaromír; Ozaniak Střížová, Zuzana; Suchánek, Vojtěch; Šimonek, Jan; Vachtenheim, Jiří; Lischke, Robert (Journal of cardiothoracic surgery, 2025)
BACKGROUND: Pulmonary hernia is a rare condition characterized by the protrusion of lung tissue through a chest wall defect. Trauma and thoracic surgery are the most common causes of acquired lung hernias. We present an unusual case of (sequential) bilateral lung herniation with parenchymal infarction after bilateral lobar lung transplantation. CASE PRESENTATION: A 50-year-old female, wait-listed as high-urgency candidate, with a body mass index (BMI) of 29 kg/m2 underwent a bilateral lobar lung transplantation for pulmonary fibrosis through a clamshell thoracotomy approach. Due to a size mismatch, stapler resection of the segment 3 and the middle lobe of the right lung, as well as an upper left lobectomy was required. The chest was closed with 3 braided non-absorbable pericostal sutures on each side. Sternal osteosynthesis was performed with a titanium sternal splint along with 7 self-tapping screws with a length of 18 mm. On the posttransplant day (PTD) 18, patient's clinical condition deteriorated. Physical examination didn't reveal any palpable subcutaneous chest resistance. However, a computed tomography (CT) scan showed a herniation of the segment 6 of the right lung. During acute surgical revision, perioperative finding revealed posterior pericostal suture failure. Therefore, a stapler resection was performed due to the infarction of the herniated segment. On the PTD 36, herniation of the left lung parenchyma was detected by acute CT scan. The protruding vital parenchyma was surgically repositioned without necessity of resection. Two posterior pericostal sutures were broken, and distal part of sternal splint detached. Thoracotomy was closed using 5 braided non-absorbable sutures. Sternum was re-osteosynthesized with the STRATOSTM system. After 3 months of intensive postoperative care, the patient was transferred to the rehabilitation department. She was discharged on the PTD 99. After 20 months of follow-up, lung function remains stable without the need for oxygen support. CONCLUSION: Clamshell incision remains ultimate approach in thoracic surgery. However, pulmonary herniation after clamshell thoracotomy is a rare complication and may manifest as acute respiratory distress syndrome with an inflammatory response. In these cases, CT scan should be always considered, even if no palpable pathology of chest is present.
Keywords: počítačová rentgenová tomografie; Hernia; Humans; Herniorrhaphy; lidé středního věku; hernie; Lung Transplantation; Female; Lung; infarkt; lidé; plicní nemoci; Thoracotomy; plíce; Infarction; Postoperative Complications; pooperační komplikace; ženské pohlaví; Middle Aged; Lung Diseases; Tomography, X-Ray Computed; operace kýly; torakotomie; transplantace plic